Remineralization rates, recycling, and storage of carbon in Amazon shelf sediments - Aller, R.C.; Blair, N.E.; Xia, Q.; Rude, P.D. (Continental shelf research, 1996)
Diagenetic reactions and redox properties of Amazon shelf sediments are characterized by extensive vertical and lateral regions of Fe and Mn cycling. This is in contrast to many temperate estuarine and shelf deposits where S can dominate early diagenesis, but may be typical of wet-tropical regions draining highly weathered terrain with energetic coastlines. Although the major pathways of C org remineralization in surfical sediments apparently differ from previously studied areas, the absolute magnitude and relative importance of benthic decomposition on the Amazon shelf are comparable to many shallow water regions of equivalent depth range (10–40 m). Net ΣC0 2 production over the upper ∼1–2 m of deposits is >50 mmol m −2 d −1 and has a predominantly planktonic isotopic composition (δ 13C∼−21to−22%‰), indicating that marine organic matter largely drives diagenesic reactions and that >20% of average water-column primary production is metabolized on the seafloor. The ΣCO 2 production rates in the upper 0–5 cm of sediment tend to increase slightly alongshelf away from the turbid river mouth, but are relatively uniform within cross-shelf transects any given season and independent of net sedimentation rate. Near uniformity in surface decomposition rates, despite substantial offshore increases in water-column productivity and net accumulation at the delta front, implies rapid cross-shelf particle exchange by estuarine circulation and tidal currents. Build-up patterns of pore-water ΣCO 2 indicate in some cases that the upper ∼20 cm was deposited only a few days prior to core collection. Benthic ΣC0 2 production is highest during periods of low or falling river flow, but no dramatic seasonality occurs. O 2 penetrates ∼2–4 mm into sediments and diffusive OZ uptake averages ∼13 mmol m −2 d −1 annually. Anaerobic metabolism accounts for >75% of sedimentary remineralization, but C/S burial ratios are usually >6 (average world shelf |2.8). Seasonal patterns in sedimentary Fe oxidation states indicate that sediments can be partially reoxidized to depths ∼0.6–1 m during erosion/redeposition and that subsequent Fe reduction can account for much of the anaerobic decomposition. Diffusive ΣC0 2 fluxes and pore-water inventories imply substantial loss of remineralized C to authigenic sedimentary-carbonate formation or flux imbalances due to nonsteady-state ingrowth of disturbed pore-water profiles. Reoxidation of metabolites and nutrient release to the water column occur during massive physical remobilization of sediments. The total benthic N remineralization flux (recycled) is comparable to external riverine and shelf-upwelling fluxes. During stable seabed periods, however, little or no co-remineralized N (N 4 +, N0 3 −, NO 2 − or P escapes diffusively into overlying water, indicating the potential for loss of up to ∼100% of the benthic remineralized N (by denitrification) and P (during authigenic mineral precipitation and adsorption). Overall, the shelf apparently acts as an efficient, fluidized-bed denitrification processor (∼50% recycled N) but an inefficient burial sink for riverine and upwelled N. In contrast to the atmospheric sink for N, rapidly regenerated P is eventually lost to the open ocean during sediment resuspension and desorption into the overlying water. Approximately 90% of the remineralized ΣCO 2 production flux escapes the sediment and ∼10% is permanently buried as authigenic carbonate. Despite reoxidation and carbonate dissolution during reworking, net burial of C is ∼5 x 10 12 g C total per year, of which ∼25–30% is carbonate from remineralized organics (∼70% of this fraction is marine) ∼20% is residual marine C org, and the remaining (∼50% is residual terrestrial C org. “Refractory” terrestrial POC is apparently subject to repetitive co-oxidation and redox cycling, resulting in remineralization of ∼65–70% of input and leaving less than ∼30–35% of the riverine POC flux stored on the shelf.